Eco-friendly control of Trichodinid infestation in Nile tilapia Oreochromis niloticus using Psidium guajava leaf extract - ANDI SULISTIAWATI; GUNARTO LAMATA; SRIWULAN SRIWULAN (Asian Journal of Agriculture, 2025)
Abstract. Sulistiawati A, Lamata G, Sriwulan. 2025. Eco-friendly control of Trichodinid infestation in Nile tilapia Oreochromis niloticus using Psidium guajava leaf extract. Asian J Agric 9: 498-506. Trichodinid ectoparasites are among the most detrimental pathogens in Nile tilapia (Oreochromis niloticus) aquaculture, causing tissue damage, growth suppression, and high mortality, particularly in small-scale systems. Chemical treatments such as formalin remain common but raise concerns regarding toxicity, environmental contamination, and pathogen resistance. Developing eco-friendly, plant-based alternatives is therefore crucial for sustainable aquaculture. This study evaluated the antiparasitic efficacy, safety, and histopathological impacts of ethanol extract of guava (Psidium guajava) leaves against Trichodinid infections in Nile tilapia. Juvenile tilapia (n=120) were naturally infected through cohabitation and randomly assigned to four treatments (0, 10, 20, and 30 ppm extract; three replicates each). Acute toxicity tests determined a 24 h LC50 value of 43.65 ppm. Extract efficacy was assessed through prevalence, infection intensity, survival rate, water quality, and histopathology, analyzed by one-way ANOVA with Tukey’s post hoc test (?=0.05). The 30 ppm treatment significantly reduced Trichodinid prevalence from 70.0% to 43.3% and infection intensity from 5.4 to 3.2 parasites per fish, representing 38.1% and 41.3% reductions, respectively (p<0.05). The highest survival rate occurred at 10 ppm (93.3%), compared to 86.7% at 20 ppm, 80.0% at 30 ppm, and 66.7% in the control. Water quality (temperature, dissolved oxygen, pH) remained within optimal culture ranges. Histopathological observations confirmed milder epithelial erosion, necrosis, and gill lamella fusion in treated groups relative to controls. These findings demonstrate that guava leaf ethanol extract, particularly at 10-30 ppm, is an effective, safe, and environmentally friendly antiparasitic agent. Its integration into aquaculture health management could reduce reliance on synthetic chemicals, promote fish welfare, and support the sustainability of tilapia farming systems.